2016
DOI: 10.1097/sla.0000000000001361
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Surgeons’ Case Selection, Morbidity, and Mortality Following Board Certification

Abstract: Objective The purpose of this study is to determine if patient selection varies based on years of surgical practice. Summary Background Data The impact of hospital and surgeon volume as a marker of experience has demonstrated an inverse association with surgical outcomes. However, temporal measures of experience often demonstrate no effect. Additionally, a self-reporting survey demonstrated decreasing case complexity over time, suggesting that changes in patient selection may account for some of these observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This stands in contrast to the findings in other specialties, such as The Cognitive Changes and Retirement among Senior Surgeons Study (CCRASS), which found that surgeons self‐reported an increase in case volume and a decrease in case‐complexity over time 5 . The CCRASS was supported by a study that showed that general surgeons with fewer than 15 years in practice operated on patients of higher preoperative risk 6 . Another study of vascular surgeons showed that surgeons within their first 5 years of practice had a greater proportion of nonelective cases with a higher degree of comorbidities and larger aneurysms 11 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This stands in contrast to the findings in other specialties, such as The Cognitive Changes and Retirement among Senior Surgeons Study (CCRASS), which found that surgeons self‐reported an increase in case volume and a decrease in case‐complexity over time 5 . The CCRASS was supported by a study that showed that general surgeons with fewer than 15 years in practice operated on patients of higher preoperative risk 6 . Another study of vascular surgeons showed that surgeons within their first 5 years of practice had a greater proportion of nonelective cases with a higher degree of comorbidities and larger aneurysms 11 .…”
Section: Discussionmentioning
confidence: 64%
“…There have been very few studies on this topic, however, the little evidence that exists in general surgery points to earlier‐career surgeons receiving more challenging and higher‐risk cases 5–7 . In cardiac surgery, a prior study showed that surgeons with lower risk‐adjusted mortality rates tended to perform CABG surgery on higher risk patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This stands in contrast to the findings in other specialties, such as The Cognitive Changes and Retirement among Senior Surgeons Study (CCRASS), which found that surgeons self-reported an increase in case volume and a decrease in case complexity over time 4 . The CCRASS was supported by a study which showed that general surgeons with fewer than 15 years in practice operated on patients of higher pre-operative risk 5 . Another study of vascular surgeons showed that surgeons within their first 5 years of practice had a greater proportion of nonelective cases with a higher degree of comorbidities and larger aneurysms 10 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few studies on this topic, however the little evidence that exists in general surgery points to earlier-career surgeons receiving more challenging and higher-risk cases [4][5][6] . In cardiac surgery, a prior study showed that surgeons with lower risk-adjusted mortality rates tended to perform CABG surgery on higher risk patients 7 .…”
Section: Introductionmentioning
confidence: 99%